Health system resilience: An urgent need to mitigate the future unprecedented pandemic - Asniar, Asniar (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Health system resilience: An urgent need to mitigate the future unprecedented pandemic